Equity in the twenty-first century workplace - Strachan, G.; Burgess, John; French, E. (Edward Elgar Publishing, 2011)
Issues of equity and inequity have always been part of employment relations and are a fundamental part of the industrial landscape. For example, in most countries in the nineteenth century and a large part of the twentieth century women and members of ethnic groups (often a minority in the workforce) were barred from certain occupations, industries or work locations, and received less pay than the dominant male ethnic group for the same work. In recent decades attention has been focused on issues of equity between groups, predominantly women and different ethnic groups in the workforce. This has been embodied in industrial legislation, for example in equal pay for women and men, and frequently in specific equity legislation. In this way a whole new area of law and associated workplace practice has developed in many countries. Historically, employment relations and industrial relations research has not examined employment issues disaggregated by gender or ethnic group. Born out of concern with conflict and regulation at the workplace, studies tended to concentrate on white, male, unionized workers in manufacturing and heavy industry (Ackers, 2002, p. 4). The influential systems model crafted by Dunlop (1958) gave rise to The discipline’s preoccupation with the ‘problem of order’ [which] ensures the invisibility of women, not only because women have generally been less successful in mobilizing around their own needs and discontents, but more profoundly because this approach identifies the employment relationship as the...